CONDITIONS OF IMPLEMENTING STATE POLICY HEALTHCARE SYSTEM REFORM IN UKRAINE - Lytvynenko M.V. (Pressing Problems of Public Administration, 2017)
Conditions of successful reformation of the health care system in Ukraine are explored.